MICA immune complex formed with alpha 3 domain-specific antibody activates human NK cells in a Fc-dependent manner. Issue 1 (6th August 2019) - Du, Changchun; Bevers, Jack; Cook, Ryan; Lombana, T. Noelle; Rajasekaran, Kamalakannan; Matsumoto, Marissa; Spiess, Christoph; Kim, Jeong M.; Ye, Zhengmao
Abstract : Background: One of the mechanisms by which tumors evade immune surveillance is through shedding of the major histocompatibility complex (MHC) class I chain-related protein A and B (MICA/B) from their cell surface. MICA/B are ligands for the activating receptor NKG2D on NK and CD8 T cells. This shedding reduces cell surface levels of MICA/B and impairs NKG2D recognition. Shed MICA/B can also mask NKG2D receptor and is thought to induce NKG2D internalization, further compromising immune surveillance by NK cells. Methods: We isolated human primary NK cells from normal donors and tested the suppressive activity of soluble recombinant MICA in vitro. Utilizing a panel of novel anti-MICA antibodies, we further examined the stimulatory activities of anti-MICA antibodies that reversed the suppressive effects of soluble MICA. Results: We show that suppressive effects of soluble MICA (sMICA) on NK cell cytolytic activity was not due to the down-regulation of cell surface NKG2D. In the presence of an α3 domain-specific MICA antibody, which did not obstruct NKG2D binding, sMICA-mediated NK cell suppression was completely reversed. Reversal of NK cell inhibition by sMICA was mediated by immune complex formation that agonized NKG2D signaling. Furthermore, this restorative activity was dependent on antibody Fc effector function as the introduction of Fc mutations to abrogate Fc receptor binding failed to reverse sMICA-mediated NK cell suppression. Furthermore, MICA immune complexes preformed with an α3 domain-specific antibody (containing a wild-type Fc) induced IFN-γ and TNF-α secretion by NK cells in the absence of cancer cells, whereas MICA immune complexes preformed with the Fc effectorless antibody failed to induce IFN-γ and TNF-α secretion. Finally, we demonstrated that MICA immune complexes formed with the α3 domain-specific antibody activates NKG2D on NK cells leading to the release of IFN-γ. Conclusions: Our results demonstrate that an α3 domain-specific MICA antibody can circumvent sMICA-mediated suppression of NK cell cytolytic activity. Moreover, our data suggest that MICA immune complexes formed with α3-specific antibodies can activate NKG2D receptor and restore NK cell function in a Fc-dependent manner. The clinical utility of α3 domain-specific MICA/B antibodies may hold great promise as a new strategy for cancer immunotherapy.